Consequences and Possible Predictors of Health-damaging Behaviors and Mental Health Problems in Pregnancy – A Review - Ulrich, F.; Petermann, F. (Geburtshilfe und Frauenheilkunde, 2016)
In recent decades, the understanding of the short and longer term effects of health-damaging behaviors and mental health problems in pregnant women and the underlying mechanisms of these behaviors and illnesses has significantly increased. In contrast, little is known about the factors affecting individual pregnant women which contribute to health-damaging behaviors and mental illness. The aim of this paper was therefore to summarize the current state of research into the consequences of nicotine and alcohol consumption, malnutrition, excessive weight gain or obesity, and impaired mental health (depression and anxiety) during pregnancy. In addition, the characteristics of pregnant women which increase their risk of developing such behaviors or mental disorders are described. A better knowledge of these risks should make it easier for clinicians to identify cases at risk early on and put measures of support in place. A review of the literature has shown that certain characteristics of pregnant women (e.g. her relationship with her partner, a previous history of mental illness prior to pregnancy) are associated with various health-damaging behaviors as well as with impaired mental health. Affected women often show an accumulated psychosocial stress which was already present prior to the pregnancy and which may persist even after the birth of the child.
Keywords: early identification; predictors; risk factors; pregnancy; review